Rapid diagnostic method for discriminating two types of COI sequences in the gall‐forming aphid Tetraneura nigriabdominalis (Hemiptera: Aphididae) by multiplex polymerase chain reaction. Issue 2 (11th December 2012) - Lee, Wonhoon; Otsuki, Akiko; Akimoto, Shin‐ichi
Abstract Tetraneura nigriabdominalis (Sasaki, 1899) is a galling aphid that is distributed widely in Eurasia. In the present study, a diagnostic multiplex polymerase chain reaction (PCR) protocol was developed to discriminate two types of the cytochrome oxidase subunit I (COI) sequences in this species, and its usefulness was examined from 25 samples of T. nigriabdominalis. Multiplex PCR and electrophoresis revealed that 10 and 15 samples had one band of 133 bp (type A) and 426 bp (type B), respectively. This discrimination was identical to the division of the 25 samples based on the alignments of COI sequences (511 bp), indicating high accuracy of this protocol in distinguishing the two types. This protocol is useful for studying microgeographic distributions of the two types and genetic diversities in T. nigriabdominalis.